LAMPU LED BAWAH AIR SEBAGAI ALAT BANTU PEMIKAT IKAN PADA BAGAN APUNG - Eko Sulkhani; Ari Purbayanto; Sugeng Hari Wisodo; Wazir Mawardi (Jurnal Teknologi Perikanan dan Kelautan, 2014)
Study on LED underwater lamp as fish aggregating device was conducted todesign and construct the LED underwater lights, to analyze strength of materials used, to analyze the light illumination value and distribution generated from the lamp, and to describe and analyze the test results of the underwater LED lights constructed. This study was divided into three stages, the material testing activities, designing and constructing the LED activities, and the field trials. Based on the results showed that the value of the maximum load that can be retained by the resin ranged from 914.27 to 1177.34 kgf/cm2. The value of the maximum load that can be held by acrylic ranges from 1238.65 to 1539.30 kgf/cm2. Design of instrument built for use in the water, with the material and acrylic resin as a protection/ waterproof. Designof the lamps weremade integrated with a CCTV camera system to facilitate the detection of fish. The LED lights used were a type of RGB High Power LED of 10 watt connected with waterproof driver adjustable step down CC-CV (QSKJ) led driver IN: DC.7-35V OUT: DC.2-30V. The number of drivers used were as many as 9 pieces, where the top of the lamp every 6 pieces of light connected with 1 driver for each color, while for the bottom of every 3 pieces of light connected with 1 pieces driver for each color. The results of measurements of the intensity of light at air showed medium that emits blue light, the most high intensity light than red and white. Type of fish caught during the 5 timesfishing trip was as much as 8 species, consisting of Auxis sp., Loligo sp., Rastrelliger sp., Trichiurus sp., Sardinella sp., Decapterus sp., and Leiognathus sp. The results of tests performed during 5 times fishing trip showed dominant catch of Leiognathus sp. as much as 288 species, and Loligo sp. as much as 266 species.